The social evolutionary dynamics of antibiotic resistance in Pseudomonas aeruginosa infections - Crosse, DJM (2019)

(untitled)
The maintenance of cooperative behaviours, and understanding why cooperation sometimes breaks down, is one of the most important questions in evolutionary biology. Antibiotic resistance in bacteria can be a cooperative behaviour, so social evolutionary theory may provide an important perspective on the problem of antimicrobial resistance, which is one of the greatest challenges to modern medicine. Bacteria engage in many social behaviours, which often involve production of a public good. One such potential public good is the resistance enzyme beta-lactamase, which degrades beta-lactam antibiotics. Public good producers are vulnerable to exploitation by non-producing cheats, which in this case would be antibiotic-sensitive cells. It is not known whether such cooperator-cheat dynamics are seen in clinical infections, but understanding if sensitive cheats arise, and the circumstances which allow this, could help control antibiotic resistance. In this thesis I examine the social dynamics of antibiotic resistance in chronic infections, concentrating on beta- lactamase production. I use a longitudinally sampled collection of the opportunistic pathogen Pseudomonas aeruginosa from cystic fibrosis patients to track how beta- lactamase production and beta-lactam resistance change during infection. I find that there is negligible increase in beta-lactamase in chronic infection. This is contrary to expectation if selection for resistance is the dominant pressure, but consistent with social dynamics. However, I do also find an increase in resistance to beta-lactams, which may reflect the contribution of other resistance mechanisms in addition to beta- lactamase production. I find a divergence in both beta-lactamase production and in beta-lactam resistance, which is correlated with treatment with beta-lactam antibiotics. This suggests beta-lactams are selecting for both high and low beta- lactamase producers, consistent with social dynamics. I compare these results to change in resistance in aminoglycoside and quinolone antibiotics, whose resistance mechanisms have less potential for sociality. In contrast to beta-lactams, I find limited divergence in aminoglycoside resistance and no divergence in quinolone resistance, as predicted by social evolutionary theory. I then take high beta-lactamase producing clinical isolates and show that beta-lactamase is a public good which can protect non- producers from beta-lactam antibiotics, allowing non-producers to invade in some instances. I show that high producers partially compensate for the presence of non- producers by making more beta-lactamase. I also show that the benefits to the non- producer primarily accrue after the cost of synthesis to the producer. These latter two findings may help stabilize cooperation against cheats. Overall, my thesis supports the suggestion that social evolutionary dynamics are important in antibiotic resistance in chronic infections.